Chitosan-based nanocomposites as coatings and packaging materials for the postharvest improvement of agricultural product: A review. (1st June 2023) - Saberi Riseh, Roohallah; Vatankhah, Masoumeh; Hassanisaadi, Mohadeseh; Kennedy, John F.
Abstract: The perishability nature of harvested fruits and vegetables, along with the effect of environmental factors, storage conditions, and transportation, reduce the products' quality and shelf-life. Considerable efforts have been allocated to alternate conventional coatings based on new edible biopolymers for packaging. Chitosan is an attractive alternative to synthetic plastic polymers due to its biodegradability, antimicrobial activity, and film-forming properties. However, its conservative properties can be improved by adding active compounds, limiting microbial agents' growth and biochemical and physical damages, and enhancing the stored products' quality, shelf-life, and consumer acceptability. Most of the research on chitosan-based coatings focuses on antimicrobial or antioxidant properties. Along with the advancement of polymer science and nanotechnology, novel chitosan blends with multiple functionalities are required and should be fabricated using numerous strategies, especially for application during storage. This review discusses recent developments in using chitosan as a matrix to fabricate bioactive edible coatings and their positive impacts on increasing the quality and shelf-life of fruits and vegetables. Graphical abstract: The application of chitosan-based nanocomposites as coatings and packaging of agricultural products. Unlabelled Image Highlights: Chitosan is a safe biopolymer for coating and packaging of agricultural products. Chitosan coatings enriched with antimicrobial agents preserve product from pathogens. Chitosan coatings enriched with calcium salts increase physical strength of products. Chitosan-based nanocomposites can be applied as films for packaging of products. Enriching chitosan with anti-browning agents increases shelf-life of products.